Ishana depicted with four arms holding a trishula - Temples of India Project Team (Jio Institute, 2024)
Ishana is depicted with four arms, holding a trishula (trident) and sarpa (snake) in his upper hand. He is holding a kamandalu (water pot) and varadaksha in his lower hands. He wears a jatamukuta (crown of matter hair) and is adorned with jewels. At the bottom right, his mount, the bull, is carved.